The VAK Model In Cultural Arts and Craft Learning: An Effort to Enhance Understanding of the Dynamic Movement of Tari Umbul in Elementary School Education - Ai Sutini; Serlina Agustin; Shafira Mustika (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
(Visual, Auditory, Kinesthetic) learning model in improving students’ understanding of movement dynamics in the traditional Tari Umbul dance, taught through the Cultural Arts and Craft (SBdP) subject in elementary school. The research was conducted at SDN Sindangwangi with 15 third-grade students as participants. Using a pre-experimental one-group pretest-posttest design, data were collected through cognitive and psychomotor tests, observation, and documentation. The VAK model was integrated into four structured learning sessions that combined visual media (videos, slides), auditory elements (verbal explanation, music), and kinesthetic activities (direct dance practice). The results showed a significant increase in both cognitive and psychomotor learning outcomes. The mean pretest score for cognitive skills was 58.3 and increased to 81.6 in the posttest, while the mean psychomotor score rose from 50.5 to 82. The N-gain scores were 0.56 for cognitive and 0.64 for psychomotor domains, both categorized as moderate effectiveness. Statistical analysis using the Wilcoxon signed-rank test confirmed that the improvement was significant (p < 0.05). Observational data also supported these results, showing higher student engagement, confidence, and motivation during VAK-based instruction. The study concludes that the VAK model not only provides a meaningful multisensory learning experience but also contributes to the enrichment of culturally responsive pedagogy in elementary schools. By integrating local cultural content with multisensory strategies, this approach strengthens active learning, supports holistic student development, and offers a practical framework for enhancing the preservation and transmission of traditional arts within formal education.